Effect of chromium supplementation on rhythmic alterations in growth performance and nutrient utilization of growing cattle during heat stress. Issue 7 (9th August 2021) - Keshri, Anchal; Roy, Debashis; Kumar, Vinod; Kumar, Muneendra; Kushwaha, Raju; Vaswani, Shalini; Kotresh Prasad, C; Prakash, Atul; Choudhury, Soumen
ABSTRACT: The present experiment was conducted to examine whether the supplementation of different organic Cr sources would improve the performance of heat-stressed calves. Twenty-four female Hariana calves were divided into four treatments (six calves per treatment): (1) calves fed on basal diet (0 mg Cr/kg DM); (2) calves fed on basal diet supplemented with 1.0 mg Cr/kg DM as Cr-picolinate (Cr-Pic); (3) calves fed on basal diet supplemented with 1.0 mg Cr/kg DM as Cr-polynicotinate (Cr-Polynic); and (4) calves fed on basal diet supplemented with 1.0 mg Cr/kg DM as Cr-yeast (Cr-Yeast). Supplementation of different sources of organic Cr did not alter the physiological response, feed utilization and growth performance of heat-stressed calves during 120-day experimental period. Nutrient digestibility and absorption of Cu, Fe and Mn were also found similar among the groups; however, utilization of Zn and Cr was higher ( P < 0.05) in Cr-supplemented calves. This study suggests that the supplementation of different sources of Cr at 1.0 mg/kg DM improves the utilization of Zn and Cr ( P < 0.05) in Cr-supplemented calves.